1990
DOI: 10.1002/jcp.1041420122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a continuously applied compressive pressure on mouse osteoblast‐like cells (MC3T3‐E1) in vitro

Abstract: Bone metabolism is often affected by a variety of mechanical forces, but the cytological basis of their action is not known. In this study, we examined the effect of a continuously applied compressive pressure (CCP) on the growth and differentiation of clonal mouse osteoblast-like cells (MC3T3-E1) cultured in a specifically devised culture chamber. The gas phase of the chamber was maintained at a pressure of 2 atmospheres (atm) above ambient (3 atm total, 3.1 kg/cm2; 3.0 x 10(5) Pa) by continuously infusing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
1
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(63 citation statements)
references
References 23 publications
(15 reference statements)
1
59
1
2
Order By: Relevance
“…3), whereas bone formation was not observed under the filter. Previous study has reported that the continuously applied compressive pressure inhibits osteoblastic differentiation in vitro (Ozawa et al, 1990). Therefore, we assume that the continuously applied pressure from the filter to the bone surface might downregulate osteoblastic differentiation of cells under the membrane filter, whereas much less pressure under the pin hole might be favorable to the osteoblastic differentiation.…”
Section: Discussionmentioning
confidence: 90%
“…3), whereas bone formation was not observed under the filter. Previous study has reported that the continuously applied compressive pressure inhibits osteoblastic differentiation in vitro (Ozawa et al, 1990). Therefore, we assume that the continuously applied pressure from the filter to the bone surface might downregulate osteoblastic differentiation of cells under the membrane filter, whereas much less pressure under the pin hole might be favorable to the osteoblastic differentiation.…”
Section: Discussionmentioning
confidence: 90%
“…Continuous hydrostatic pressure at physiologic levels decreased osteoclast formation in marrow cultures (Rubin et al, 1997), and increased production of PGE 2 and decreased collagen synthesis from osteoblast-like cells (Ozawa et al, 1990). Application of intermittent compressive force to fetal mouse calvariae was shown to increase bone formation and decrease bone resorption (Klein-Nulend et al, 1987).…”
Section: What Mechanical Factors Are Generated By Loading?mentioning
confidence: 99%
“…The restoration of compressive loads to articular cartilage stimulates synthesis of GAGs and increases the thickness of cartilage (De Witt et al, 1984;Palmoski and Brandt, 1984;Slowman and Brandt, 1986;Kiviranta et al, 1987). The application of mechanical loads to bone has been shown to: (i) increase the percentage of cells synthesizing DNA (Hasegawa et al, 1985), (ii) alter the types of protein synthesized (Hasegawa et al, 1985), (iii) alter the rate of bone formation and resorption (Vargas and Raisz, 1990), (iv) alter calcification (Ozawa et al, 1990), and (v) inhibit osteoblast differentiation (Imamura et al, 1990;Ozawa et al, 1990;Vargas and Raisz, 1990). Both the condyle and the temporal bone undergo degenerative changes if the disk is deranged, perforated, or removed (Scapino, 1983;Ericsson and Westesson, 1985).…”
Section: (B) Blomechanical Factors and Degenerative Temporomandibularmentioning
confidence: 99%